THE IMPLEMENTATION OF TECHNICAL INTEROPERABILITY MODELS IN LARAS VERSION 1.0 DIGITAL LIBRARY APPLICATIONS:A CASE STUDY IN THE CENTER FOR SCIENTIFIC DOCUMENTATION AND INFORMATION – INDONESIAN INSTITUTE OF SCIENCES - Hendrawan, Muhammad Rosyihan (Association of Indonesian Library and Information Professionals, 2018)
This study aims to find out models implementation of the technical interoperability applied and developed on the Digital Library Applications of the Library and Archive Analysis System version 1.0 (LARAS v 1.0) by the Center for Scientific Documentation and Information-Indonesian Institute of Sciences (PDII-LIPI). The other goal of this study is to determine why PDII-LIPI tries to develop LARAS v 1.0 and has changed the previous application of WINISIS. This study was done by using a case study method with qualitative approach. Data was collected by documents analyses and in-depth interviews. This result of the study shows that LARAS v 1.0 was created by developers at PDII-LIPI to avoid the obsolescence of information and technology communication (ITC), in this case, is the digital library application. In fact, the conflicts between the developers and the librarians in developing LARAS v 1.0 still exist. Models implementation of technical interoperability applied to LARAS is a combination of several levels of Level of Information System Interoperability (LISI) model. Nevertheless, in practice, LARAS v 1.0 is still not perfect, especially from the point of view of system development of metadata, encoding, communication protocol, databases, and indexing.